1990
DOI: 10.1177/002076409003600306
|View full text |Cite
|
Sign up to set email alerts
|

A Two Year Follow Up of New Long-Stay Patients in an Inner City District General Hospital

Abstract: In 1967 Magnus described 'the new chronics', patients admitted to a psychiatric hospital who then stayed for more than one year. Since that time many studies have examined this patient group but the majority have focussed on psychiatric hospital populations. There is some doubt, however, as to whether the characteristics of new-long stay patients in District General Hospital (DGH) psychiatric in-patient units are comparable. The current paper describes a two year follow-up study of Medium and New-Long Stay pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
2

Year Published

1992
1992
2005
2005

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 16 publications
0
2
0
2
Order By: Relevance
“…Patients who occupy in-patient psychiatric beds for prolonged periods have attracted interest in the UK for over 25 years. They have been the focus of two national surveys (Mann & Cree, 1976; as well as local studies (Lawrence et al, 1988;O'Driscoll et al, 1990;Patrick & Holloway, 1990;Clifford et al, 1991;Thornicroft et al, 1992;Kurian et al, 1994;Rowlands et al, 1998;Holloway et al, 1999). A need for longer-term provision for this group was demonstrated by a survey of acute inpatient units, which found that 46% of new long-stay patients were considered inappropriately placed but remained as in-patients on account of their need for specialised rehabilitation places (Shepherd et al, 1997).…”
mentioning
confidence: 99%
“…Patients who occupy in-patient psychiatric beds for prolonged periods have attracted interest in the UK for over 25 years. They have been the focus of two national surveys (Mann & Cree, 1976; as well as local studies (Lawrence et al, 1988;O'Driscoll et al, 1990;Patrick & Holloway, 1990;Clifford et al, 1991;Thornicroft et al, 1992;Kurian et al, 1994;Rowlands et al, 1998;Holloway et al, 1999). A need for longer-term provision for this group was demonstrated by a survey of acute inpatient units, which found that 46% of new long-stay patients were considered inappropriately placed but remained as in-patients on account of their need for specialised rehabilitation places (Shepherd et al, 1997).…”
mentioning
confidence: 99%
“…A maior parte da literatura disponível relacionada a acompanhamento de paciente após internação integral, refere-se a diagnósticos específicos e a taxas de recaídas, o que dificulta a comparação com nossos dados. 24 Se considerarmos o diagnóstico mais grave -esquizofrenia -podemos encontrar estudos que mostram uma evolução mais favorável do que se pensava há algumas décadas. 21 O acompanhamento de pacientes esquizofrênicos por cinco anos após a alta mostrou que apenas 19% tiveram prejuízo grave no desempenho social.…”
Section: Discussionunclassified
“…27 Por outro lado, um menor tempo de internações psiquiátricas tem sido defendido desde a década de 60; portanto, o correspondente aumento de serviços comunitários de apoio intensivo adequados para o período após a alta é necessário, 16 evitando assim o surgimento dos "novos crônicos das UP". 24 O fato de os pacientes com maior tempo de internação terem melhor desempenho está indicando a necessidade de um cuidado intensivo por maior tempo, o que não significa que isso deva ocorrer com o paciente internado. Serviços extra-hospitalares poderiam atender essa necessidade sem os prejuízos causados por uma internação integral prolongada.…”
Section: Discussionunclassified
“…Referral was signi® cantly associated with a diagnosis of affe ctive disorder or schizophrenia. Patrick and Holloway (1990) described a two-year follow-up study of m edium term and new long-stay patients identi® ed w ithin an inner-city district general hospital in 1986 and found that elderly patients with affe ctive disorders and also with organic brain syndrom es were particularly highly represented. K ayser-Jones and K app (1989) have used a case study to illustrate the im portance of advocacy roles on behalf of nursing hom e residents.…”
Section: Com M Unity Services For Grad Uatesmentioning
confidence: 99%